EVALUATING NPF OF MURABAHA SETTLEMENT STRATEGY: PERSPECTIVE OF RISK MANAGEMENT AND DSN MUI'S FATWA - Said Rafli Ridha; Fithriady; Mulia, Rika (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2023)
Non-Performing Financing (NPF) is one of the indicators in evaluating bank performance. Financing products with murabaha contracts are one of the products that dominate the Islamic banking industry where the percentage of its NPF will also affect profits. This study examines the strategy implemented by one of the Bank Syariah Indonesia (BSI) Area Office in Aceh Province towards Murabaha NPF from two perspectives, risk management and Fatwa DSN-MUI using a descriptive approach. The results conclude that in handling NPF, banks begin with negotiation/mediation approach, then gradually rescheduling, restructuring, reconditioning, execution of collateral/auctions and litigation. Those steps are in accordance with risk management concept in terms of preventing NPF and consistent with Fatwa DSN-MUI in terms of NPF settlement. However, among the obstacles are bad character debtors so that the settlement process will take a long period of time and keep being suspended. This is certainly a significant viewpoint for banks that educating and socializing the management of financing must be explained from the beginning and ensure that debtors understand all related applicable bank regulations. Keywords: Murabaha Financing, Non-Performing Financing, Risk Management, Fatwa DSN-MUI, Islamic Banks